Geochemical and Isotopic Evidence for Provenance of the Western Sea of Japan Over the Last 30000 Years - Dou, Ruxi; Zou, Jianjun; Shi, Xuefa; Zhu, Aimei; Dong, Zhi; Gorbarenko, Sergey; He, Lianhua; Gao, Jingjing; Zhang, Ying; Cui, Jingjing (Frontiers in Earth Science, 2021)
The Sea of Japan (JS) is a unique marginal sea in the western North Pacific that is characterized by four shallow straits. It can provide information about the paleoenvironment, for instance indicating variations in the East Asian Monsoon, Tsushima Warm Current, sea ice coverage, and Westerly Jet. Compared with other marginal seas in the western North Pacific, the JS is currently the only marginal sea without influx from large rivers. It is, therefore, of interest to determine the source of terrigenous sediments over time, particularly in the western JS, which has been less investigated in previous reports. In this study, a suite of multi-proxies including Sr and Nd isotopes and minor elements were measured for fine fractions (<63 μm) of core LV53-18-2 that were recovered from the western JS over the last 30 ka. Our results show that the sediments are rich in volcanic detritus and that the provenance of terrigenous sediments in the western JS is mainly derived from the arid region in northern China and coastal areas in the Far East. During the Last Glacial Maximum, the increased coverage of sea ice may have contributed to the accumulation of terrigenous debris. Meanwhile, the stronger East Asian Winter Monsoon and expansion of the Westerly Jet over northern China also carried more dust to the study area. However, the weakened atmospheric circulation and rise in sea level, induced by the ascending boreal insolation during the last deglaciation and early Holocene, remarkably reduced input of terrigenous debris, and the intense melting of sea ice delivered an amount of detritus from coastal areas to the research area. After 8 ka, the high stand sea level and opening of the Tatar Strait may have led to the development of the Liman Cold Current, which transports large quantities of volcanic materials to the study area continuously and produces more positive Eu anomalies, radiogenic εNd, and depleted ΣREE.